(untitled) (Bangladesh Agronomy Journal, 2017)
Experiment was carried out at the Agronomy field of Bangladesh Rice Research Institute, Gazipur, during the period from December 2014 to May 2015 to investigate the response of different levels of N and methods of weeding on weed abundance and grain yield of BRRI hybrid dhan3 under alternate wetting and drying (AWD) irrigation condition. The treatments consisted of five N levels viz.,0, 60, 120,180 and 240 kg N ha-1 and four different weed control methods viz., Pre-emergence herbicide followed by 1HW, Pre-emergence followed by post emergence herbicide, Weed free by 3 hand weedings and Unweeded (control). The experiment was laid out in factorial RCB design with three replication. Pre-emergence application of prefer 18WP (Bensulfuran Methyl + Acetachlor) and post emergence herbicide Dhaman 300wp (Bispyribac sodium 18% + Bensulfuran methyl 12%) followed by one hand weeding effectively control all weeds (78-93%). In the experimental field, sedges and grass weeds were highly dominant over treatments. Based on summed dominance ratio (SDR), the most dominant weed species could be arranged in the order of Echinochloa crus-galli > Scirpus juncoides > Cynodon dactylon > Cyperus difformis > Marselia minuta > Monochoria vaginalis. Interaction of nitrogen levels and weeding methods had significant response on yield and yield components of hybrid rice. The highest (7.61 t ha-1) grain yield was obtained from the combination @ 180 kg N ha-1 with weed free treatments. Comparable higher grain yield was obtained from the combination of pre emergence herbicide of bensulfuranm methyl + acetachlor) + one hand weeding with 180 kg N ha (7.48 t ha-1) and the combination of pre + post-emergence herbicide (Bispyribac sodium 18% + Bensulfuran methyl 12%) with 180 kg N ha-1 (7.56t ha-1). The estimated optimum dose of nitrogen for Pre EH, Post EH and 3HW (weed free) were 173, 189.1 and 189.4 kg N ha-1 respectively for BRRI hybrid dhan3 under AWD irrigation system. Bangladesh Agron. J. 2017, 20(1): 13-24